Application of Wet Nanostructured Bacterial Cellulose as a Novel Hydrogel Bioanode for Microbial Fuel Cells. Issue 3 (27th January 2017) - Mashkour, Mehrdad; Rahimnejad, Mostafa; Mashkour, Mahdi; Bakeri, Gholamreza; Luque, Rafael; Oh, Sang‐Eun
Abstract: In this study, wet bacterial cellulose (BC) with a water content of more than 98% was utilized as a novel scaffold to design bioanodes for microbial fuel cells (MFCs). At first, unmodified wet BC was used a bioanode. Then a simple in situ synthesis of polypyrrole (PPYR) at various pyrrole concentrations was subsequently performed on the BC's fibers to generate the novel bioanodes. Characterization of the BC‐PPYR nanobiocomposites was conducted by using ATR‐FTIR, XRD, and FESEM. The performance of the nanobiocomposites was studied in a MFC system by using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and polarization curves. A power density of 136 mW/m 2 and a current density of 662 mA/m 2 were found for BC‐PPYR, which are superior to those of graphite (1 mW/m 2 and 9 mA/m 2, respectively). The results were attributed to a good adhesion of bacterial cells to the fibrous surface of BC, permanent capillary transfer of nutrients, the conductive content of hydrogel BC, and good conductivity and catalytic activity of PPYR in the nanocomposite. Abstract : A permanent change : Bacterial cellulose (BC) is wet nanostructured porous framework for fabricating a biocompatible anode for microbial fuel cells. Polypyrrole, as a conductive polymer, improves the conductivity of BC and boosts the generated power density. With this new bioanode, because of capillaries between BC fibers and permanent transfer of nutrients, the risk of microorganism spoilage and clogging of the pores in the anode become minimized.